Efficiency Meets Safety: Transforming Operating Theatre‐To‐Paediatric Intensive Care Unit Transfers in a Paediatric Hospital - Adel Sharadgah; Shabaan Osman; Rajnish Kumar; Iman Darwish; Victoria Shaward; Hisham Obeidat; Jihad Zahra; Reda Elsahy; Hisham Abdulla (Nursing in Critical Care, 2026)
ABSTRACT Background Transfers from the Operating Theatre (OT) to the Paediatric Intensive Care Unit (PICU) represent a high‐risk transition for critically ill children. At a Tertiary Paediatric Hospital, the absence of a standardised handover protocol resulted in prolonged recovery waits of up to 120 min, medication errors, haemodynamic instability, and reduced family and staff satisfaction. Aim To enhance patient safety, reduce handover time, and improve family and staff satisfaction through a structured Operating Theatre‐to‐PICU handover process. Study Design Single‐centre, pre–post quality improvement project in a 23‐bed tertiary PICU. A multidisciplinary, co‐designed intervention comprising a two‐phase telephone checklist, a standardised shared drug library, preloaded infusion pumps delivered to OT, a dedicated receiving nurse and structured pre‐arrival family orientation. Training was delivered by link nurses, using Kotter's change model. Results Handover duration decreased by approximately 50% (15–20 to 8–10 min) following implementation. No transfer‐related medication errors occurred across the 77 protocol cases, versus six across 96 baseline transfers and haemodynamic instability attributable to infusion changes was virtually eliminated. Family satisfaction scores were higher in post‐implementation cohorts (87% at 3 months; 90% at 6 months) than pre‐intervention (72%), as were staff satisfaction scores (80% and 95% vs. 58%). Mean PICU length of stay decreased from 5.2 to 4.6 days. Conclusions A structured, multi‐component handover process improved patient safety, handover efficiency, and family and staff experience during OT‐to‐PICU transfers, sustained at 6 months. Relevance to Clinical Practice The intervention demonstrates that a multidisciplinary handover protocol can reduce transfer‑related risks and enhance family and staff experience during high‑risk transitions from the Operating Theatre‐to‐PICU.